SUB1 varieties increased rice (Oryza sativa) yield in flood-prone rainfed lowlands of coastal regions - SARANGI, SUKANTA K; SINGH, S; MAJI, B; SHARMA, P C; SRIVASTAVA, A K; BURMAN, D; MANDAL, S; KRISHNAMURTHY, S L; SINGH, U S; ISMAIL, A M (The Indian Journal of Agricultural Sciences, 2020)
Submergence of lowland rice (Oryza sativa L.) fields during the wet season in coastal regions adversely affects survival and productivity of rice. A field experiment was conducted for two consecutive wet seasons in 2016 and 2017 at ICAR-Central Soil Salinity Research Institute, Regional Research Station, Canning Town, West Bengal to evaluate the performance of six varieties carrying the SUB1 gene (BR11-Sub1, Ciherang-Sub1, CR1009-Sub1, IR64- Sub1, Samba-Sub1, and Swarna-Sub1) along with two checks (DRR Dhan39 and Sabita) under stagnant and flash flooding situations. Sabita produced the highest grain yield (3.45 t/ha) followed by CR1009-Sub1 (3.27 t/ha) under stagnant flooding. Sabita is the local check under stagnant flooding. Under flash flooding, CR1009-Sub1 produced the highest grain yield of 4.11 t/ha, followed by Swarna-Sub1 (3.11 t/ha) and BR11-Sub1 (2.78 t/ha). Participatory varietal selection (PVS) was conducted during both the years to assess the preferences of farming communities for these varieties. Under stagnant flooding, the highest preference score was recorded for Sabita (0.62) followed by BR11-Sub1 (0.32) and CR1009-Sub1 (0.31). The lowest preference score was observed for IR64-Sub1 (-0.56), Samba-Sub1(-0.31), and Ciherang-Sub1 (-0.26). Under flash flooding, the highest preference score was recorded for CR1009-Sub1 (0.63) followed by BR11-Sub1 (0.38) and Swarna-Sub1 (0.20). The lowest preference score was observed for IR64-Sub1 (-0.62), Samba-Sub1 (-0.34), Ciherang-Sub1 (-0.29), and DRR Dhan39 (-0.27). Based on the results of field experiments and farmers’ preferences, CR1009-Sub1, BR11-Sub1, and Swarna-Sub1 could be recommended for cultivation in areas affected by flash floods in coastal areas of India.